STRATEGI DIVERSIFIKASI PRODUK KAYU OLAHAN Acacia mangium (studi kasus : PT. Musi Hutan Persada) - Hamzah Hamzah; Marimin Marimin; Imam Teguh Saptono (Jurnal Manajemen & Agribisnis, 2005)
The objective of this study is to suggest  the best wood  products of Acacia mangium  that have  high value-added as an alternative business and to formulate the fitting  strategy. This study  is descriptive case study applying  purposive sampling method which involved wood product Experts and Senior PT. Musi Hutan Persada Management.  Data have been analyzed through Exponential Compare Method (MPE) to select the best product alternative based on eleven set criteria, using AHP method, Hayami value-added Analysis, and Cost Analysis.  The study shows that there are five superior Acacia mangium based products, namely 1) Sawnwood and woodworking (KGKO), 2) Furniture, 3) Medium Density Fibreboard (MDF), 4) Tannin-glue of Acacia mangium  bark and 5) Wood Charcoal.  And  Sawnwood and Woodworking (KGKO), Furniture, and   Tannin-glue  have the best chance.  Best business strategy to be adhered by MHP, “related-diversification”, then is  to continue utilizing  Acacia mangium wood  as renewable resources,  integrated and sustainable business.